2011
DOI: 10.1021/ic101249k
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Copper Complexes Based on Parallel β-Diiminato Binding Sites and their Reactions with O2: Evidence for a Cu−O−Cu Entity

Abstract: Investigations concerning the system β-diketiminato-Cu(I)/O(2) have revealed valuable insights that may be discussed in terms of the behavior of mononuclear oxygenases containing copper. On the other hand nature also employs dinuclear Cu enzymes for the activation of O(2). With this background the ligand system [(Me(2))(C(6)H(3))Xanthdim](2-) containing two parallel β-diiminato binding sites linked by a xanthene backbone with 2,3-dimethylphenyl residues at the diiminato units was investigated with respect to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 76 publications
6
43
0
6
Order By: Relevance
“…Numerous studies revealed that the nature of phenol and ligands as well as the reaction conditions are crucial factors that have a strong impact on the oxidation selectivity [25,34,[60][61][62][63][64][65][66]. In 1959, Hay and co-workers discovered the oxidative C-O coupling of 2,6-dimethylphenol to poly(2,6-dimethyl-1,4-phenyleneoxide) (PPO), an important plastic in engineering, in the presence of a homogeneous Cu(I) catalyst and amines (usually pyridine) [61].…”
Section: Coppermentioning
confidence: 99%
“…Numerous studies revealed that the nature of phenol and ligands as well as the reaction conditions are crucial factors that have a strong impact on the oxidation selectivity [25,34,[60][61][62][63][64][65][66]. In 1959, Hay and co-workers discovered the oxidative C-O coupling of 2,6-dimethylphenol to poly(2,6-dimethyl-1,4-phenyleneoxide) (PPO), an important plastic in engineering, in the presence of a homogeneous Cu(I) catalyst and amines (usually pyridine) [61].…”
Section: Coppermentioning
confidence: 99%
“…As described in a recent review [358], synthetic complexes with this core are relatively rare, in part because of their tendency to react readily with water to yield bis(μ-hydroxo)dicopper(II) complexes [359][360][361][362]. In a recent resurgence of interest in these species, ligands 110 and 111 ( Figure 52) have been used to prepare and characterize species proposed to contain (μ-oxo)dicopper(II) cores [363,364]. In both cases, these species formed upon treatment of dicopper(I) complexes with O 2 or PhIO.…”
Section: (μ-Oxo)dicopper Complexesmentioning
confidence: 99%
“…In both cases, these species formed upon treatment of dicopper(I) complexes with O 2 or PhIO. For the system comprising 110, the (μ-oxo)dicopper(II) product was identified on the basis of UV-vis absorption spectroscopy and resonance Raman spectroscopy, but more complete characterization was hindered by its thermal instability [363]. Ligand 111 led to a more stable complex 112, which was more fully characterized, including by EXAFS (Cu-Cu ¼ 2.91 Å), NMR spectroscopy, high-resolution electrospray ionization mass spectrometry, and DFT calculations [364].…”
Section: (μ-Oxo)dicopper Complexesmentioning
confidence: 99%
“…25 In more recent years, the chemistry of copper β-diketiminate has been expanded to include both dinucleating and trinucleating ligands. [29][30] As part of studies toward elucidation of the rare dicopper(II) mono(oxo) functional group, Limberg and coworkers have suggested that, within a xanthene-spaced dinucleating ligand framework a dicopper mono(µ-oxo) species may be formed from reaction of a 4:1 ratio of Cu:O2. 29 Murray and co-workers have reported a remarkable tricopper(I) dinitrogen complex formed within a carefully designed paracyclophane ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30] As part of studies toward elucidation of the rare dicopper(II) mono(oxo) functional group, Limberg and coworkers have suggested that, within a xanthene-spaced dinucleating ligand framework a dicopper mono(µ-oxo) species may be formed from reaction of a 4:1 ratio of Cu:O2. 29 Murray and co-workers have reported a remarkable tricopper(I) dinitrogen complex formed within a carefully designed paracyclophane ligand. 30 As a first step to new dinuclear complexes containing low-coordinate copper sites within flexible and easily modified ligand frameworks, we now report synthetic approaches to a series of dicopper(I) complexes supported by dinucleating β-diketiminate ligands.…”
Section: Introductionmentioning
confidence: 99%